Identification of leucine-rich repeat receptor-like protein kinase (LRR-RLK) genes in paper mulberry and their potential roles in response to cold stress. (April 2022) - Su, Yalei; Peng, Xianjun; Shen, Shihua
Abstract: Leucine-rich repeat receptor-like protein kinases (LRR-RLKs) represent the largest group of receptor-like kinases in plants, which have been previously reported to play vital roles in plant growth, development, stress adaptation and signal transduction. However, there is lack of comprehensive analysis of this family in paper mulberry ( Broussonetia papyrifera ). In the present investigation, a genome-wide scan revealed the presence of 236 LRR-RLK genes in paper mulberry, which were classified into 21 subgroups based on the maximum-likelihood phylogenetic tree. Gene structure and conserved motif analyses suggested genes in the same subgroup had highly consistent motif composition and intron/exon arrangement, but were divergent among subgroups. Total of 223 BpLRR-RLK genes were unevenly distributed across all 13 chromosomes, while the remaining 13 genes were localized to the unassembled scaffolds. Tandem and segmental duplications were confirmed to contribute to the expansion of BpLRR-RLK family. Further Ka/Ks showed that the duplicated BpLRR-RLKs had experienced strong purifying selection. The global promoter composition, transcriptome and phosphorylation analysis indicated that many of BpLRR-RLKs were associated with plant development, biotic and abiotic stress response, especially for cold stress. Furthermore, protein-protein interaction network was constructed for the 127 and 14 BpLRR-RLKs that responded to cold stress at the transcriptomics and phosphorylation level, respectively. All these findings will facilitate the studies on the evolutionary history of the LRR-RLK gene family in paper mulberry, also establish a solid foundation to further explore the potential functions of LRR-RLK genes in higher plants, particularly with regards to cold resistance. Graphical Abstract: ga1 Highlights: Totally 236 BpLRR-RLK family genes were firstly identified via genome-wide screening. Both tandem duplications and segmental duplications played vital roles in the expansion of BpLRR-RLK gene family. The divergent expression patterns of LRR-RLKs were found in various tissues and different developmental stages of paper mulberry. Some BpLRR-RLK genes were sensitive to cold stress. The LRR-RLK gene family might be participated in cold signal pathway in paper mulberry